Membangun Karakter Generasi Berakhlak di Tengah Kemajuan Teknologi Abad 21 - Elpia, Elpia; Asriati, Nuraini (Universitas Tanjungpura, 2024)
The advancements in technology in the 21st century have brought significant changes to various aspects of life. The presence of the internet, artificial intelligence, and other digital technologies has facilitated access to information, communication, and innovation. However, these advancements also pose new challenges, particularly in shaping the character of the younger generation with moral integrity. Building a strong character based on moral values amid the rapid flow of technology is crucial to ensure that future generations are not only intellectually capable but also possess good ethics. Technology in the 21st century has created a fast-paced, globally connected world. Developments such as artificial intelligence, big data, and the digital revolution have transformed the way we live, work, and interact. In this era, the challenges faced by the education sector extend beyond enhancing academic competencies; they also involve how to cultivate a morally upright character in the youth amid the currents of digital globalization. This article examines the importance of character education in fostering a generation with strong moral and ethical values, despite living in an environment saturated with technological advancements. Through a literature analysis and examples of character education implementation in various institutions, this article demonstrates that the success of character formation relies heavily on an integrated approach involving technology, formal education, and the roles of family and society. In conclusion, technology can serve as an effective tool to support character education if utilized wisely and with appropriate guidance. Relevant and contextual character education in the 21st century is essential for creating a generation that is not only intelligent but also possesses integrity and strong ethical values.